Relationship between interest and mathematics performance in a technology-enhanced learning context in Malaysia - Wong, Shu Ling; Wong, Su Luan (Springer, 2019)
The primary aim of this preliminary study is to examine a possible association between interest and mathematics performance among Malaysian students in a technology-enhanced learning environment. The Mathematics Interest Inventory was administered to 40 students to measure students’ interest towards mathematics, while a mathematics test was used to measure students’ mathematics performance. Results of the descriptive statistical analyses revealed that the students were relatively interested in mathematics. Correlational analyses showed that interest was not significantly correlated to mathematics performance among the students. Nevertheless, a significant relationship between interest and mathematics performance was found among students who had lower mathematics performance. The findings of this study pointed to the importance of igniting interest among students with lower mathematics performance given its strong link to mathematics performance. The Interest-Driven Creator theory served as an anchor in the theoretical framework of the study and it was discussed within the context of mathematics learning.